Early Hippocampal Synaptic Loss Precedes Neuronal Loss and Associates with Early Behavioural Deficits in Three Distinct Strains of Prion Disease - CUNNINGHAM, COLM (My University, 2013)
Prion diseases are fatal neurodegenerative diseases of the CNS that are associated with the accumulation of misfolded cellular prion protein. There are several different strains of prion disease defined by different patterns of tissue vacuolation in the brain and disease time course, but features of neurodegeneration in these strains have not been extensively studied. Our previous studies using the prion strains ME7, 79A and 22L showed that infected mice developed behavioural deficits in the same sequence and temporal pattern despite divergent end-stage neuropathology. Here the objective was to address the hypothesis that synaptic loss would occur early in the disease in all three strains, would precede neuronal death and would be associated with the early behavioural deficits. C57BL/6 mice inoculated with ME7, 79A, or 22L-infected brain homogenates were behaviourally assessed on species typical behaviours previously shown to change during progression and euthanised when all three strains showed statistically significant impairment on these tasks. A decrease in labelling with the presynaptic marker synaptophysin was observed in the stratum radiatum of the hippocampus in all three strains, when compared to control animals. Negligible cell death was seen by TUNEL at this time point. Astrocyte and microglial activation and protease resistant prion protein (PrPSc) deposition were assessed in multiple brain regions and showed some strain specificity but also strongly overlapping patterns. This study shows that despite distinct pathology, multiple strains lead to early synaptic degeneration in the hippocampus, associated with similar behavioural deficits and supports the idea that the initiation of synaptic loss is a primary target of the misfolded prion agent.
PUBLISHED
Keywords: Animal behavior; Astrocytes; Burrowing; Glucose metabolism; Hippocampus; Microglial cells; Neuronal death